2004
DOI: 10.1007/s10151-004-0087-z
|View full text |Cite
|
Sign up to set email alerts
|

An uncomplicated and safe way to perform on-table colonic lavage

Abstract: When surgery is performed in patients with acute or sub-acute left-colonic obstruction, the method of antegrade on-table colonic lavage is well established. In this short note, a modification of the original procedure is presented that makes it even more uncomplicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…However, there is continuing debate on the practice of one‐stage surgery . For an obstructed left colon, various surgical approaches have been described as a total/subtotal or segmental colectomy and primary anastomosis accompanied by decompression of the distended colon manually, or by using a tube with or without irrigation . In selected patients, colonic stenting is another option as a bridge to elective surgery .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is continuing debate on the practice of one‐stage surgery . For an obstructed left colon, various surgical approaches have been described as a total/subtotal or segmental colectomy and primary anastomosis accompanied by decompression of the distended colon manually, or by using a tube with or without irrigation . In selected patients, colonic stenting is another option as a bridge to elective surgery .…”
Section: Discussionmentioning
confidence: 99%
“…During the 1980s, segmental colectomy with ICI was suggested as an alternative approach . Since then, finding the most effective method for on‐table lavage has been of great clinical interest . It has been reported that the main concerns associated with ICI are prolonged operative time, risk of contamination, and lack of expertise .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today primary resection has become standard practice to treat patients with an obstructed left colon [2][3][4][5][6]. Initial insertion of an enteral stent to decompress the obstructed colon, allowing surgery to be performed electively, is gaining popularity [7], although mature data from large randomized trials are awaited.…”
Section: Introductionmentioning
confidence: 99%